Implementing an Empowerment Framework: The Significance for Children's Play Environments and Reflective Practice - Natalie Canning (MDPI AG, 2022)
This paper examines implementing a unique way of observing children's play through an empowerment framework; considering children's choices, decisions, and interactions through an empowerment lens. The study considers the different ways children are empowered through their play environments using participation, voice, and ownership as three guiding themes and the challenges of recording children's empowerment for practitioners. Five nested case studies in two different UK-based childcare environments form the basis of the research. Thematic analysis scrutinised the data that were generated from observations of children's play, interviews with practitioners and a focus group with both settings. A phenomenological theoretical framing allowed a layered picture of empowerment to emerge. Practitioners made subjective yet informed judgements about children's empowerment in their observations, drawing on knowledge and understanding of children's personalities. Empowering experiences were recorded under prompt questions focusing on the way in which and the influences of how children were experiencing empowering moments. Observing through an empowerment framework has changed practice and the way practitioners think about the opportunities provided for children in their play environment. The main challenges for practitioners relate to anxiety around moving away from outcome-based observations and time limitations on producing meaningful narratives around children's empowerment.